Genetic diversity of the submerged macrophyte Ceratophyllum demersum depends on habitat hydrology and habitat fragmentation - Engloner, Attila I.; Németh, Kitti; Kós, Péter B.; Meglécz, Emese; Bereczki, Judit (Frontiers in Plant Science, 2023)
The adaptability of plant populations to a changing environment depends on their genetic diversity, which in turn is influenced by the degree of sexual reproduction and gene flow from distant areas. Aquatic macrophytes can reproduce both sexually and asexually, and their reproductive fragments are spread in various ways (e.g. by water). Although these plants are obviously exposed to hydrological changes, the degree of vulnerability may depend on the types of their reproduction and distribution, as well as the hydrological differences of habitats.The aim of this study was to investigate the genetic diversity of the cosmopolitan macrophyte Ceratophyllum demersum in hydrologically different aquatic habitats, i.e. rivers and backwaters separated from the main river bed to a different extent. For this purpose, the first microsatellite primer set was developed for this species.Using 10 developed primer pairs, a high level of genetic variation was explored in C. demersum populations. Overall, more than 80 % of the loci were found to be polymorphic, a total of 46 different multilocus genotypes and 18 private alleles were detected in the 63 individuals examined. The results demonstrated that microsatellite polymorphism in this species depends on habitat hydrology. The greatest genetic variability was revealed in populations of rivers, where flowing water provides constant longitudinal connections with distant habitats. The populations of the hydrologically isolated backwaters showed the lowest microsatellite polymorphism, while plants from an oxbow occasionally flooded by the main river had medium genetic diversity.The results highlight that in contrast to species that spread independently of water flow or among hydrologically isolated water bodies, macrophytes with exclusive or dominant hydrochory may be most severely affected by habitat fragmentation, for example due to climate change.Hydrological Forecasting Service 2023.